(untitled) (International Journal of Management and Sustainability, 2022)
E-commerce is a new, rising phenomenon in Southeast Asian countries, and online payment methods are becoming increasingly popular on e-commerce platforms. Despite increasing investments in e-commerce platforms’ online payment systems, Vietnamese consumers are still doubtful about this innovative payment alternative. This research applied the Technology Acceptance Model (TAM) to analyze the variables affecting customers’ intention to make online payments on e-commerce platforms in Vietnam, a potential Southeast Asian market. In addition, the research group expanded on the primary study by adding the variables of Subjective Norms, Trust, and Risk to validate the findings of the original work in the new context. A new factor suitable for Vietnamese conditions, Payment Intermediary, was included by the authors to better explain the consumers’ attitudes and intentions toward online payments. The surveys were carried out using two methods of basic random sampling: an offline approach at offices and schools, and an online approach using social media. 521 questionnaires were collected, and 448 were considered valid and met the requirements that were initially set. SPSS 26 was used to assess the consistency and validity of all variables and test the hypotheses using a regression model. The hypothesis model was verified. The results showed that the correlation between independent and dependent variables, namely Attitude toward Use and Intention to Use, is very clear. In consumers’ use of e-commerce platforms, Payment Intermediary plays a crucial role in developing their online payment attitudes and intentions.